Fabrication of novel agrowaste (banana and potato peels)-based biochar/TiO2 nanocomposite for adsorption of Cr(VI), statistical optimization via RSM approach - Ashfaq, Aamna; Nadeem, Raziya; Gong, Hongyu; Rashid, Umer; Saima Noreen; Rehman, Shafique ur; Ahmed, Zubair; Adil, Muhammad; Akhtar, Nayab; Ashfaq, Muhammad Zeeshan; Alharthi, Fahad A.; Kazerooni, Elham Ahmed (Multidisciplinary Digital Publishing Institute, 2022)
In this research work, a simple, efficient, and eco-friendly procedure for the biosorption of Cr(VI) ions was studied. A detailed comparative study was performed to check the adsorption efficiency of agrowaste (banana and potato peels)-based adsorbents. Firstly, mixed biosorbent was washed, dried and ground into powder, secondly, biosorbent was pyrolyzed into biochar and thirdly TiO2 nanocomposite (TiO2 NC) biosorbent was made by sonicating using prepared biochar and TiO2 NPs. Titanium dioxide nanoparticles (TiO2 NPs) were synthesized by a green method using Psidium guajava leaf extract. The synthesized adsorbents were characterized by SEM, EDX FT-IR, XRD and UV-visible analysis. The effect of four different factors, i.e., pH of the synthetic metallic solution, time, concentration and adsorbent dosage was studied. The optimum conditions were time (120 min), pH (3), concentration (10 ppm) and adsorbent dosage (1.0 g). The kinetic modeling showed that the adsorption of Cr(VI) ion follows a pseudo second-order mechanism and the Langmuir isotherm model was found to fit better for this study. Response surface methodology (RSM)-based optimized parameters provided optimal parameter sets that better represent the adsorption rate models. The uptake capacity of Cr(VI) from aqueous solution was found to be biomass (76.49 mg/L) ˂ biochar (86.51 mg/L) ˂ TiO2 NC (92.89 mg/L). It can be suggested that the produced TiO2 NC could possibly be an efficient biosorbent for the removal of Cr(IV).